Planning and the Paradox of Conscious Purpose - Gary J. Coates (Oz, 1980)
Since the discovery of fire, and in the past 7,000-10,000 years with the development of agriculture and the establishment of fixed settlements, the evolution of human culture has been the reverse of that of organic systems…